Tumor shrinkage and improved quality of life in a heavily pretreated metastatic breast cancer patient treated with eribulin. (November 2013) - La Verde, Nicla; Piva, Sheila; Ganzinelli, Monica; Farina, Gabriella; Gherardi, Giorgio; Girelli, Serena; Bramati, Annalisa; Del Re, Luca; Damia, Giovanna
Eribulin mesylate is approved for the treatment of metastatic breast cancer after progression with anthracyclines and taxanes. Here we report the case of a woman with triple-negative breast cancer who, after nine lines of chemotherapy, showed striking primary tumor shrinkage and regression of metastatic lesions with eribulin treatment. This response allowed the patient to undergo debulking surgery. Even though the patient was heavily pretreated, eribulin was well tolerated and improved her quality of life. Biological analysis of tumor specimens was performed to investigate the underlying mechanism of action of the drug.